Analysis of the Clinical Characteristics of Spontaneous Bile Duct Perforation in Children - Yan, Xueqiang; Zheng, Nannan; Jia, Jinfu; Kuang, Houfang; Lei, Haiyan; Bian, Hongqiang; Qin, Xinke; Sun, Xuan; Duan, Xufei; Zhan, Jianghua (Frontiers in Pediatrics, 2022)
Objective This study aimed to explore the etiology, clinical features, diagnosis, and treatment of spontaneous bile duct perforation(SBDP) in children. Methods The clinical data of children with SBDP admitted to Wuhan Children's Hospital from January 2014 to January 2020 were retrospectively analyzed. Results Twenty-eight cases of children with SBDP (males: 28.6%; females: 71.4%; male-to-female ratio, 1:2.5; average age, 2.15 years) were analyzed. The most common symptoms were fever (85.7%), nausea and vomiting (78.6%), and distension (67.9%). Among them, 26 patients(92.9%) were with elevated hypersensitive C-reactive protein, 24 patients(85.7%) were with increased neutrophil percentage, and 22 patients(78.6%) were with raised peripheral blood leukocyte count. Moreover, 19 patients(67.9%) were with increased serum total bilirubin level, and 5 patients(17.9%) were with an elevated conjugated bilirubin level. Abdominal CT examination revealed that the patients’ gallbladder wall was thickened with edma, accompanied by gallbladder stenosis, gallbladder mucosa enhancement, and hydrops was found in the abdominal cavity and lesser omental bursa. Twenty-two patients underwent abdominal paracentesis, and 20(90.9%) of them were exposed to bile-based ascites. Among these patients, four were recovered with conservative treatment, whereas the others(85.7%) were surgically investigated. Of the twenty-four patients, the perforation site was found at the union of the hepatic tube and cystic duct in 12 cases (50%), no perforation site was observed in 9 cases(37.5%) , and the common hepatic duct was noted in 3 cases(12.5%). Twenty-four patients underwent stage Ⅰ surgery, and temporary biliary drainage was performed because of severe abdominal inflammation. Cholangiography and enhanced CT revealed the abnormal location of the pancreatic duct joins the bile duct in 64.3% patients. After surgery, 15 patients underwent stage Ⅱ biliary tract reconstruction. Follow-up after 3 months to 6 years indicated that the patients recovered well with no serious complications. Conclusion SBDP in children may be related to pancreaticobiliary malunion(PBM) and congenital weakness of the bile duct wall. The clinical manifestations of this condition lack specificity, but this limitation can be assisted through diagnosis via abdominal CT and performing abdominal paracentesis. Once the SBDP diagnosis is confirmed, the patient should follow the principle of individualized treatment.